The Influence of Financial Risk Tolerance on Investment Decision-Making in a Financial Advice Context - Linh T.M. Nguyen; Gerry Gallery; Cameron Newton (Australasian Accounting, Business and Finance Journal, 2016)
Client risk tolerance is universally assessed in the advisory process to help financial advisers provide suitable advice that assists clients in their investment decision-making. Although there is a well-established literature on risk tolerance and decision-making, little is known about financial risk tolerance and its influence on investor decisions in the financial advice context. Thus, the purpose of this study is to examine this influence with a focus on the key expected risk tolerance determinants: client financial literacy, trust in the financial advice service, and relationship length with the service. A new theoretical model and related hypotheses were proposed and tested using survey data from financial adviser clients in Australia (N=538). Results revealed a positive relationship between client risk tolerance and investment decision-making. Further, client trust and relationship length with the service were found to be positively associated with client financial literacy and risk tolerance. These findings, which provide a more comprehensive understanding of how risk tolerance and its antecedents influence client decisions, have the potential to improve advice in the financial services industry.
Keywords: Risk tolerance; individual investment decisions; client-adviser relationship; financial advice context; financial planning